Non-congruence of high-temperature mechanical and structural behaviors of LaCoO3 based perovskites. Issue 4 (April 2017) - Aman, Amjad; Jordan, Ryan; Chen, Yan; Stadelmann, Richard; Lugovy, Mykola; Orlovskaya, Nina; Payzant, E. Andrew; dela Cruz, Clarina; Reece, Michael J.; Graule, Thomas; Kuebler, Jakob
Abstract: This paper presents the mechanical behavior of LaCoO3 and La0.8 Ca0.2 CoO3 ceramics under four-point bending in which the two cobaltites are subjected to a low stress of ∼8 MPa at temperatures ranging from room temperature to 1000 °C. Unexpected stiffening is observed in pure LaCoO3 in the 700–900 °C temperature range, leading to a significant increase in the measured Young's modulus, whereas La0.8 Ca0.2 CoO3 exhibits softening from 100 °C to 1000 °C, as expected for most materials upon heating. Neutron diffraction, X-ray diffraction and micro-Raman spectroscopy are used to study the crystal structure of the two materials in the RT–1000 °C temperature range. Despite a detailed study, there is no conclusive evidence to explain the stiffening behavior observed in pure LaCoO3 as opposed to the softening behavior in La0.8 Ca0.2 CoO3 at high temperatures (above 500 °C).